DIVERSIFIKASI KEFIR BERBASIS KEDELAI DENGAN VARIASI KONSENTRASI SUSU SKIM DAN INOKULUM - Tina Nurkhoeriyati; Dionisius Yusuf; Ihsan Iswaldi; Abdi Christia; Vania Gisella (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Physicochemical and sensory characteristics of commercial kefir were evaluated to be used as the benchmark for the development of soybean-based kefir with various concentrations of skim milk and inoculum. The commercial kefir has alcohol content and titratable acidity values in accordance with the Codex standards. A Quantitative Descriptive Analysis (QDA) was carried out to obtain the description of kefir as the reference for the development of soybean-based kefir. Sensory evaluation of soybean-based kefir samples with various concentrations of skim milk and inoculum was conducted by trained panelists. Based on sensory evaluation, the soybean-based kefir with similar sensory characteristics to the commercial kefir was that made by adding 10% of skim milk and 10% kefir grains of 3, 4 and 5% (w/w). Soybean-based kefir with 10% (w/w) skim milk and 3% (w/w) kefir grains was chosen for analysis of its physicochemical characteristics. Despite having sensory characteristics similiar to commercial kefir, this soy-based kefir possesses different physicochemical properties from that of commercial one. Neverthe-less, the physico-chemical characteristics of selected kefir-based soybean met the Codex standards. The content of protein, fat, alcohol, dry matter and viscosity of the selected soy-based kefir were: 3.79±0.10% wb, 0.00±0.00% wb, 0.93±0.00%wb, 57.26 mg/kg, 8.43±0.38% wb, and 37.95±0.05 cP, respectively.